A MARKETING STRATEGY TO OPTIMIZE ZERO PERCENT INTEREST SUBSIDY ON FINANCING PRODUCTS SUBSIDIZED BY REGIONAL GOVERNMENT AT BANK SUMSEL BABEL BRANCH PAGARALAM CITY, SOUTH SUMATERA, INDONESIA: MARKETING STRATEGY TO OPTIMIZE ZERO PERCENT INTEREST SUBSIDY ON FINANCING PRODUCTS SUBSIDIZED BY REGIONAL GOVERNMENT AT BANK SUMSEL BABEL BRANCH PAGARALAM CITY, SOUTH SUMATERA, INDONESIA - Darwin, Darwin; Fransiska, Welly (Institute for Law and Economics Studies, 2025)
The world of banking is experiencing very rapid development. In this way, competition between banking products cannot be avoided and is getting tighter. One of them is financing products that are subsidized by the government, consumers and compete with other banks. The aim of this research is to analyze the marketing strategy implemented by Bank Sumsel Babel Branch Pagar Alam City Branch in increasing the number of Zero Percent Interest Subsidy financing customers on Financing Products Subsidized by the Regional Government. Quantitative approach, namely by conducting library research, namely data collection techniques using questionnaire sources with customers of Bank Sumsel Babael Financing Products, Pagar Alam City Branch. The results of this research show that the interest subsidy is zero percent on financing products that are subsidized by the regional government marketing mix marketing 4P (location, product, price and promotion). The strategy that is more often used in this case is the promotional strategy. Through promotional strategies, customers better understand the advantages and disadvantages of mu-rabahah financing products. Promotional strategies are more effective and aimed at the general public to increase the number of customers in a faster time.